"The Worst Experience of My Life": The Internship Crisis and Its Impact on Students. Issue 7 (18th March 2016) - Parent, Mike C.; Bradstreet, Tyler C.; Wood, Makenzie; Ameen, Eddy; Callahan, Jennifer L.
Abstract : Objective: The objective of the present study was to understand how internship applicants perceive themselves as being affected by the ongoing imbalance between the number of internship spots available and the number of applicants to internship. Method: The present study undertook a qualitative, and supplemental quantitative, analysis of 1, 076 internship applicant responses to an item included in the 2011 postmatch survey asking participants how the internship crisis has affected them. Results: Results indicated that the internship application process in general was viewed overwhelmingly negatively. Respondents described personal stress and system issues in their responses. Respondents described reciprocal stresses; applications spur on stresses, which are compounded by fears of not matching. Such fears cast negative light on training. Participants also described resiliencies that buffered against stresses and perceptions of discrimination or bias that add to stress. Conclusions: The implications of these findings for supporting students, working to resolve the internship crisis, and adapting policy are discussed.